2005
DOI: 10.2337/diacare.28.10.2514
|View full text |Cite
|
Sign up to set email alerts
|

High Plasma Level of Remnant-Like Particle Cholesterol in the Metabolic Syndrome

Abstract: OBJECTIVE -The metabolic syndrome is associated with a high incidence of cardiovascular disease even when the abnormalities present in the syndrome are mild. The underlying mechanism of the metabolic syndrome has not been elucidated. We investigated whether a strong atherogenic lipoprotein, remnant-like particle (RLP) lipoprotein cholesterol, is elevated in the metabolic syndrome.RESEARCH DESIGN AND METHODS -We performed a health examination among the residents of a rural community in Japan. Complete datasets,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Levels of remnant cholesterol were also higher in the NK cell 'non-increase' group. Remnant cholesterol is an indicator of atherogenic lipoproteins, and has been associated with the metabolic syndrome [23,24]. Moreover, we found that IL-6 levels remained at a significantly higher level during follow-up in the NK cell 'non-increase group' , while IL-6 levels were normalized in those with reconstituted NK cell levels.…”
Section: Discussionmentioning
confidence: 63%
“…Levels of remnant cholesterol were also higher in the NK cell 'non-increase' group. Remnant cholesterol is an indicator of atherogenic lipoproteins, and has been associated with the metabolic syndrome [23,24]. Moreover, we found that IL-6 levels remained at a significantly higher level during follow-up in the NK cell 'non-increase group' , while IL-6 levels were normalized in those with reconstituted NK cell levels.…”
Section: Discussionmentioning
confidence: 63%
“…Recently, Satoh et al (27) demonstrated that RLP cholesterol levels were elevated in metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4). Because the PDMP level is associated with MS 23) and the OR for the presence of MS in subjects with a predicted risk 8% compared to subjects with a predicted risk 8% unadjusted and adjusted for age was 4.2 (2.0 8.7) and 7.6 (2.6 21.6), respectively, we used MS, as a confounding factor, in the model. The OR adjusted for age, platelet count, hsCRP, and presence of MS was 4.3 (1.6 11.8) ( Table 4).…”
Section: Association Of the Elevated Pdmp Level With The 8% 10-yr Chdmentioning
confidence: 99%
“…These are defined as vesicles measuring less than 1.5 m in diameter that are enriched in procoagulant platelet proteins 5) and express several platelet receptors, such as CD42b (glycoprotein Ib) and teins (Rem-L) and high sensitivity C-reactive protein (hsCRP) were also reported to be associated with MS and to promote atherosclerosis 23,24) . We also reported that PDMPs were associated with positive metabolic syndrome (MS) criteria in healthy volunteers without signs, symptoms, or a history of cardio-or cerebrovascular disease and any medication 25) .…”
Section: Introductionmentioning
confidence: 99%